2009
DOI: 10.1175/2008jas2727.1
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Wave Instability Dynamics at High Reynolds Numbers. Part II: Turbulence Evolution, Structure, and Anisotropy

Abstract: This paper examines the character, intermittency, and anisotropy of turbulence accompanying wave instability, breaking, and turbulence evolution and decay for gravity waves (GW) having a high intrinsic frequency, amplitudes above and below nominal convective instability, and a high Reynolds number. Wave breaking at both amplitudes leads to an extended inertial range of turbulence, with turbulence energies that maximize within ;1 wave period of the onset of breaking. Turbulence sources include both shear and bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
98
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 89 publications
(107 citation statements)
references
References 44 publications
9
98
0
Order By: Relevance
“…Rapp and Lübken, 2004). Intensive modelling studies of turbulence generated at mesopause altitudes showed anisotropy of the turbulence fields and radar backscatter (Gibson-Wilde et al, 2000;Fritts et al, 2003Fritts et al, , 2009Fritts et al, , 2011. However, to our knowledge there is no quantitative estimation of aspect sensitivity for such turbulence so far (perhaps with the exception of Hocking and Hamza (1997) who analytically considered anisotropic turbulence due to wind-shear only).…”
Section: Discussionmentioning
confidence: 99%
“…Rapp and Lübken, 2004). Intensive modelling studies of turbulence generated at mesopause altitudes showed anisotropy of the turbulence fields and radar backscatter (Gibson-Wilde et al, 2000;Fritts et al, 2003Fritts et al, , 2009Fritts et al, , 2011. However, to our knowledge there is no quantitative estimation of aspect sensitivity for such turbulence so far (perhaps with the exception of Hocking and Hamza (1997) who analytically considered anisotropic turbulence due to wind-shear only).…”
Section: Discussionmentioning
confidence: 99%
“…GW instabilities are likewise challenging to identify and quantify because they are inherently nonlinear and multiscale, they display a wide range of possible instability structures, and observations typically lack the precision needed to enable a comprehensive description of GW and environmental parameters [see, e.g., Lombard and Riley, 1996;Sonmor and Klaassen, 1997;Fritts and Alexander, 2003;Fritts et al, 2009aFritts et al, , 2009bFritts et al, , 2013. Distinguishing between GWs that are vertically propagating and ducting events or mesospheric bores are challenging to characterize with confidence due to various remote and local potential sources and their expected sensitivity and responses to small-scale features in the environmental wind and temperature profiles [Chimonas and Hines, 1986;Fritts and Yuan, 1989;Pasko, 2003, 2008;Simkhada et al, 2009;Laughman et al, 2009Laughman et al, , 2011Walterscheid and Hickey, 2009;Snively et al, 2013].…”
Section: Introductionmentioning
confidence: 99%
“…They considered wave propagation in a rectangular region of the atmosphere having vertical and horizontal sizes of 48 and 120 km, respectively. Some authors (Fritts and Garten 1996;Andreassen et al 1998;Fritts et al 2009Fritts et al , 2011 simulated turbulence produced by breaking atmospheric waves and Kelvin-Helmholtz instabilities. Their models were three-dimensional and described waves and turbulence in rectangular boxes having limited horizontal and vertical sizes.…”
Section: Introductionmentioning
confidence: 99%